Understanding differences between apprenticeship programmes in Europe: towards a new conceptual framework for the changing notion of apprenticeship - Markowitsch, Jörg [Verfasser]; Wittig, Wolfgang [Verfasser] (My University, 2022)
„Comparative studies on ‘apprenticeships’ in Europe increasingly cover a variety of programmes previously not considered under this heading. The paper explores the potential of a new, combined cultural-historical and functional classification of apprenticeships on the basis of their underpinning training logic. Four main logics are discussed which categorise apprenticeships according to their key purpose and the responsibilities with regard to content, organisation and financing. It is argued that the typology can serve as an explanatory framework for ongoing changes in apprentice-ship approaches and may be used for the identification of similarities and common challenges.“ (authors‘ abstract; BIBB-Doku)
Keywords: I 2.2 Europa; 370; Berufsausbildung; Progamm; Internationaler Vergleich; Typologie; Europa